Kwaito Bodies : Remastering Space and Subjectivity in Post-Apartheid South Africa - Livermon, Xavier, 1973- (Book collections on Project MUSE., 2020)
"KWAITO BODIES understands kwaito, a style of house music that emerged in the years following the end of apartheid in South Africa, as both an embodiment and enactment of the freedoms that era promised. Yet post-apartheid freedoms were not clear-cut: Livermon argues that kwaito was a way for urban black youth to contest and negotiate inclusion in the nation, working through the legacies of apartheid to adopt an orientation to urban life that accommodated consumerist drives for material well-being, demands for freedom of expression, and a more complex array of genders and sexualities. The music and its accompanying cultural and stylistic practices were often critiqued for their materialism and seen as a distraction from the serious undertaking of building a free South Africa. But in connecting kwaito to practices from across the African diaspora and situating Johannesburg in Afrodiasporic space, Livermon emphasizes the varied forms of political engagement, mobility, and circulation that it enacted. Through a personal archive of cassettes, the careful study of music videos, and fifteen years of his own experiences in backyard parties, clubs, and gatherings, Livermon provides layered descriptions of the conviviality of kwaito: the gathering, dancing, and performing in the urban neighborhoods of Johannesburg and across South Africa in the 1990s. These experiences lead him to the central metaphor of remastering, which signifies not only the rearticulation of a new form, but also the possibility that this new form might be heard only as an imitation of its antecedent. For example, in chapter 3 Livermon draws out the entanglement of critique and co-optation in the neoliberal policies predominant in South Africa in the 1990s. In seeking financial stability, many kwaito entrepreneurs and artists participated in programs like Black Economic Empowerment. These programs enabled kwaito through funding, but they also formed part of the state structures of respectability that kwaito artists and audiences were actively contesting. In later chapters Livermon focuses on race/gender/sexuality in relation to the embodiment of kwaito. He furthers his discussion of a politics of pleasure through the consumption and perpetuation of racial stereotypes by prominent kwaito artists like Lebo Mathosa, whose refusal of the "bad girl" and subsequent enactment of the "dangerous woman" created space for new instantiations of black femininity (chapter 4); and Mandoza, whose performances manipulated the tsotsi (thug) character in order to test the limits of the heavily prescribed masculine roles that predominate kwaito (chapter 5). This book will interest readers in African and African diaspora studies, performance studies, cultural studies, and popular music studies, as well as readers interested in race, gender, and sexuality"--